Efficacy, Safety and Tolerability of a New 10% Intravenous Immunoglobulin for the Treatment of Primary Immunodeficiencies - Perez, Elena E.; Hébert, Jacques; Ellis, Anne K.; Alpan, Oral; Lumry, William R.; Shapiro, Ralph; Suez, Daniel; Mandujano, J. Fernando; Wasserman, Richard L. (Frontiers in Immunology, 2021)
We report here the results of a phase 3 study to assess the efficacy, safety, and tolerability of GC5107, a new 10% liquid intravenous immunoglobulin (IVIG) in preventing serious bacterial infections in patients with primary immunodeficiency (ClinicalTrials.gov: NCT02783482). Over a 12-month study period, 49 patients aged 3 to 70 years with a confirmed diagnosis of primary immunodeficiency received GC5107 at doses ranging from 319 to 881 mg/kg body weight every 21 or 28 days, according to their previous IVIG maintenance therapy. A total of 667 infusions of GC5107 were administered comprising a total of 45.86 patient-years of treatment. A single acute serious bacterial infection occurred during the study, resulting in an incidence of 0.02 events per patient-year (upper 99% one-sided confidence interval limit: 0.21), meeting the prespecified primary efficacy endpoint. The mean incidence of infections other than acute serious bacterial infections was 2.9 infections per patient-year. Efficacy was also demonstrated by the low mean annualized rate of hospitalizations due to infection (0.1 day) and the mean annualized duration of hospitalizations (0.1 day). The mean rate of intravenous and oral antibiotic use was 0.1 day and 13.2 days, respectively. There was a mean of 7.1 days of missed work, school, or daycare days. The proportion of infusions with temporally associated adverse events (TAAEs) occurring during or within 72 hours after GC5107 infusion was 0.24 (upper 95% one-sided confidence interval limit: 0.31), meeting the pre-specified primary safety endpoint. Overall, 149 of 667 infusions (22%) were associated with TAAEs. The most common TAAE was headache, reported by 49% of patients. More than 98% (731/743) of all adverse events that occurred throughout the 12-month study period were mild or moderate. More than 98% of infusions were completed without discontinuation, interruption or rate reduction. There were no treatment-emergent serious adverse events related to GC5107 or study discontinuations due to an adverse event. Overall, pharmacokinetic parameters for GC5107 were within the range of those reported in studies of other marketed IVIG products. Results of the present study demonstrate that GC5107 is an effective, safe and well-tolerated treatment for patients with primary immunodeficiency.